Optimal Beamformer Design for Millimeter Wave Dual-Functional Radar-Communication Based V2X Systems - Liu, Beiyuan; Liu, Jiajia; Kato, Nei (IEEE journal on selected areas in communications, 2022)
Millimeter wave (MmWave) dual-functional radar-communication (DFRC) technology is believed to hold the ability to alleviate spectrum congestion and inter-radar interference in 5G vehicle-to-everything (V2X) systems. The radar target sizes in V2X system may not be ignored in views of the demands of short-range sensing and ultra-narrow beams supported by massive MIMO mmWave beamforming. Under such scenario, a novel single-target-multi-beams (STMB) radar beam alignment scheme is proposed to acquire more accurate information on estimated ranges and velocities by allocating multiple radar beams to a certain target. For instance, the relative velocity direction can be accurately estimated based on STMB scheme by using a weighted linear estimation methods. Then, the hybrid analog-digital beamforming under STMB scheme is formulated and optimized by maximizing transmission rate subject to radar signal-to-interference-and-noise (SINR) constraints, where a radar beam cancellation algorithm is proposed to adjust adaptively the radar beam number pointing to a certain target, which can guarantee strict radar SINR constraint under different transmission power levels. The numerical results verify the effectiveness and reliability of STMB scheme and show that the proposed beamformer outperforms the benchmark in both spectral efficiency and minimum radar SINR.